Efficacy of a papain-based gel from indigenous papaya (Carica papaya L., var. Solo) for chemomechanical caries removal - Echegoyen, Trisha Eiko M.
INTRODUCTION: One reason for neglect of oral health stems from fear. An estimation of about 80% of patients has apprehension due to the pain and discomfort which is experienced from drilling. With the advancement of technology, addressing dental caries through minimum intervention is possible. One example of minimum intervention dentistry is by using a chemomechanical caries removal during caries excavation by hand. The objective of this study is to determine the efficacy of a papain-based gel from locally available papaya as a chemomechanical caries removal agent on teeth.